Effect of detoxification on N3 sleep correlates with brain functional but not structural changes in alcohol use disorder. (1st September 2022) - Zhang, Rui; Tomasi, Dardo; Shokri-Kojori, Ehsan; Manza, Peter; Feldman, Dana E.; Kroll, Danielle S.; Biesecker, Catherine L.; McPherson, Katherine L.; Schwandt, Melanie; Wang, Gene-Jack; Wiers, Corinde E.; Volkow, Nora D.
Abstract: Background: Sleep disturbances are very common in alcohol use disorder (AUD) and contribute to relapse. Detoxification appears to have limited effects on sleep problems. However, inter-individual differences and related brain mechanisms have not been closely examined. Methods: We examined N3 sleep and the associated brain functional and structural changes in 30 AUD patients (9 Females, mean age: 42 years) undergoing a 3-week inpatient detoxification. Patients' N3 sleep, resting state functional connectivity (RSFC), grey matter volume (GMV) and negative mood were measured on week 1 and week 3. Results: AUD patients did not show significant N3 sleep recovery after 3-weeks of detoxification. However, we observed large variability among AUD patients. Inter-individual variations in N3 increases were associated with increases in midline default mode network (DMN) RSFC but not with GMV using a whole-brain approach. Exploratory analyses revealed significant sex by detoxification effects on N3 sleep such that AUD females showed greater N3 increases than AUD males. Further, N3 increases fully mediated the effect of mood improvement on DMN RSFC increases. Conclusions: We show a significant relationship between N3 and DMN functional changes in AUD over time/abstinence. The current findings may have clinical implications for monitoring brain recovery in AUD using daily sleep measures, which might help guide individualized treatments. Future investigations on sex differences with a larger sample and with longitudinal data for a longer period of abstinence are needed. Highlights: N3 recovery during AUD detoxification was associated with increased DMN RSFC. N3 changes during detoxification were not associated with grey matter changes. Exploratory analyses showed greater N3 recovery in AUD females than AUD males. N3 recovery mediated the association between DMN RSFC and mood changes.